2013
DOI: 10.2174/1567205011310010014
|View full text |Cite
|
Sign up to set email alerts
|

Microdose Lithium Treatment Stabilized Cognitive Impairment in Patients with Alzheimer’s Disease

Abstract: A lower incidence of dementia in bipolar patients treated with lithium has been described. This metal inhibits the phosphorylation of glycogen-synthase-kinase 3-α and β, which are related to amyloid precursor protein processing and tau hyperphosphorylation in pathological conditions, respectively. Following the same rationale, a group just found that lithium has disease-modifying properties in amnestic mild cognitive impairment with potential clinical implications for the prevention of Alzheimer's Disease (AD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 0 publications
4
51
0
Order By: Relevance
“…8 Nunes and colleagues observed in a 18-month clinical study that AD patients treated daily with micro-doses of lithium performed at a consistent level on the mini-mental status exam, indicating arrested cognitive decline compared with the placebo-group. 9 Moreover, Forlenza and colleagues reported in their 1-year clinical trial study that patients with amnestic mild cognitive impairment treated with chronic low-dose lithium progressed less to AD compared with the placebo-group. 7 The treated patients performed higher on the cognition subscale of the AD Assessment Scale and had decreased concentrations of phosphorylated tau in their cerebrospinal fluid (CSF), indicating lithium as a potential therapeutic for AD.…”
mentioning
confidence: 99%
“…8 Nunes and colleagues observed in a 18-month clinical study that AD patients treated daily with micro-doses of lithium performed at a consistent level on the mini-mental status exam, indicating arrested cognitive decline compared with the placebo-group. 9 Moreover, Forlenza and colleagues reported in their 1-year clinical trial study that patients with amnestic mild cognitive impairment treated with chronic low-dose lithium progressed less to AD compared with the placebo-group. 7 The treated patients performed higher on the cognition subscale of the AD Assessment Scale and had decreased concentrations of phosphorylated tau in their cerebrospinal fluid (CSF), indicating lithium as a potential therapeutic for AD.…”
mentioning
confidence: 99%
“…Encouraging findings for targeting GSK3 have been identified in examinations of dementia development in bipolar patients that have been treated with lithium for long periods of time, as these patients often have a lower prevalence of dementia than the general population (Nunes et al, 2007; Kessing et al, 2010). Clinical trials of lithium in Alzheimer’s disease have demonstrated some beneficial effects (Forlenza et al, 2012; Nunes et al, 2013), although not in all studies (Hampel et al, 2009). An initial trial of another GSK3 inhibitor, Tideglusib, did not demonstrate remarkable protective effects in Alzheimer’s disease patients, although it was designed as a safety trial, not as a therapeutic trial (del Ser et al, 2013).…”
Section: Targeting Gsk3 Therapeuticallymentioning
confidence: 99%
“…Normally, GSK3β is constitutively expressed in all cells and primarily inhibited via phosphorylation of serine-9 [198]. Lithium can increase GSK3β phosphorylation indirectly [199], thereby reducing its tau hyperphosphorylation activity and stabilising cognitive ability in AD patients [200]. Comparison of the ratio of Ser-9-phosphorylated GSK3β versus total GSK3β in platelets of AD patients and controls revealed a significant reduction in AD and MCI samples, indicating seriously enhanced enzyme activity [54].…”
Section: Reviewmentioning
confidence: 99%